Analisis dan Desain Antena Mikrostrip untuk Komunikasi Satelit pada Frekuensi Ka-Band - Fariany Rizqa; Dharu Arseno; Trasma Yunita (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Satellite technology is a telecommunications technology where the satellite is a communication device placed in space and requires the allocation of the frequency spectrum for telecommunications services. The most widely used frequencies for satellite communication are the C-Band frequency (4 GHz to 8 GHz) and the Ku-Band frequency (12 GHz to 18 GHz). Also, Ka-Band frequency (26,5 GHz to 40 GHz) is the center of attention in the telecommunications industry nowadays because it has a large enough bandwidth to accommodate more service capacity. In this article, a microstrip antenna with a rectangular patch of four elements (array 2x2) has been designed using line feed rationing techniques that work at a frequency of 29,25 GHz (Ka-Band) for satellite communication. An appropriate antenna dimension is required so that the antenna can work and has a good performance at the expected frequency. Simulation results show a return loss value of -43,052 dB, VSWR is worth 1,014 with a bandwidth of 2,728 GHz. In addition, the resulting gain value is 7,823 dB with directional radiation patterns and ellipse polarization.